بعضُ مهارات الذكاء الوجداني وعلاقتها بتقدير الذات لدى المتفوقين في رياضة - لزنك, أحمد (Sciences de l'Homme et de la Société, 2013)
هدفت هذه الدراسة إلى الكشف عن مستويات الذكاء الانفعالي وتقدير الذات، وتمثلت مشكلة البحث في التساؤل الرئيس التالي: ما علاقة الذكاء الانفعالي بتقدير الذات لدى ممارس رياضة الكونغ فو ووشو؟.وتمثلت فروض البحث في ثلاث فرضيات تم من خلالها الإجابة عن تساؤلات الدراسة، وبلغ حجم العينة 74 رياضياً متفوقاً بنوادي الكونغ فو ووشو. وقد تم استخدام مقياسيْن للحصول على البيانات من أفراد العينة، وهما مقياس الذكاء الانفعالي ومقياس تقدير الذات. كما تم استخدام مجموعة من الأساليب الإحصائية من بينها المتوسط الحسابي وعلاقة بيرسون. وتوصلت نتائج الدراسة إلى أن متوسط درجات الذكاء الانفعالي (2.89) ومتوسط درجات تقدير الذات (2.86) وهما مستوى مرتفع، كما توصل إلى وجود علاقة ارتباط موجبة بين الذكاء الانفعالي وتقدير الذات تقدر بـ 0.626 وهي دالة إحصائيا عند مستوى الدلالة 0.01.       This study aimed at exploring the levels of emotional intelligence and self  esteem. The research problem was represented in the following main question: what is the relationship between emotional intelligence and self esteem for a Kung Fu Wushu sport  practitioner?.        Three hypotheses were to answer the questions of the research. The study sample consisted of seventy four (74) elite athletes, and a combination of scales was used, including an emotional intelligence and a self esteem scale. The researcher also used the following statistical methods: means and Pearson Correlation Coefficient.         The results revealed a high mean of emotional intelligence at 2.89 and also a high mean of self esteem estimated at 2.86.         The results also revealed that emotional intelligence was positively correlated to self esteem, with a correlation coefficient of 0.626, and a statistically significant level of 0.01.